Hemophagocytic lymphohistiocytosis during treatment of intracranial multifocal germinoma: a case report and literature review - Guo, Ting; Liu, Zichun; Chen, Yixin; Cheng, Yangyang; He, Kaitong; Lin, Xin; Wang, Mingzhu; Sun, Yihua (Frontiers in Oncology, 2024)
Hemophagocytic lymphohistiocytosis (HLH), also known as hemophagocytic syndrome (HPS), is a benign histiocytosis with hyperreactive proliferation of the mononuclear phagocyte system caused by immune function abnormalities, which often occurs under the background of genetic mutations, inflammation, infection or tumors. Because the research on malignancy-associated HLH (M-HLH) is focused on hematological malignancies, reports on HLH secondary to solid tumors are rare. In this case, we report a 14-year-old girl who developed HLH during treatment for intracranial multifocal germinoma, and the disease was controlled after hormone combined with etoposide(VP-16) and other related treatments. To our knowledge, there have been no documented cases of HLH caused by intracranial multifocal germinoma.